THE IMPACT OF TRANSFORMATIONAL LEADERSHIP ON STRATEGIC REPUTATION IN THE INDUSTRIAL SECTOR: A CASE STUDY OF THE PHARMACEUTICAL INDUSTRIES COMPANY IN SAMARRA - Eng. Dr. Ali Abdel Qader Mahmoud; Prof. Ishaq Yousef Hamdan (Scholars Digest Publishing, 2023)
The current research tests the correlation and impact between the transformational leadership variable represented in its dimensions (ideal impact, individual consideration, intellectual consultation, motivation) and the strategic reputation variable in its dimensions (social responsibility, work environment, brand), where the research problem was the role of transformational leadership in the strategic reputation in the pharmaceutical industries company in Samarra, and the questionnaire was used as a data collection tool where 92) Form for the research sample, which was selected department managers and division officials deliberately, as the main research hypothesis was the existence of a correlation and a moral impact between transformational leadership and strategic reputation and the data was analyzed using the program (SPSS) as a number of statistical methods were used to verify the validity of the hypothesis, including the correlation coefficient (person) and simple regression analysis, where the results were identical to the hypothesis of the research, it was found that there is a correlation and a significant impact between transformational leadership and strategic reputation, in the light of which a set of recommendations were formulated that it is hoped that those concerned will benefit from in the current study.
Keywords: Leadership – Transformational Leadership – Strategic Reputation.